Smart cities and circular economy : the future of sustainable urban development - Kandpal, Vinay; Santibanez-Gonzalez, Ernesto D. R.; Chatterjee, Prasenjit; Nallapaneni, Manoj Kumar (Emerald Publishing Limited, 2024)
In a world grappling with resource depletion and environmental degradation, this work empowers readers to foster sustainable urban environments, while promoting a deeper understanding of the intricate relationship between new technologies and cutting-edge economic theory. A major highlight is the presentation of a diverse range of real-world best practices. These case studies of successful integrations of Smart Cities and a Circular Economies identify the key factors that contribute to their triumph. The takeaways equip policymakers and urban planners with practical solutions for addressing the challenges of sustainable urban developments. From policy and regulatory hurdles to technological advancements, financing and investment opportunities to collaboration and stakeholder engagement, the authors offer valuable guidance for leaders and decision makers seeking to surmount barriers to integration. In sum, Smart Cities and Circular Economy is a timely, indispensable resource offering practical solutions and insights, championing the creation of sustainable and liveable urban environments. Whether you are a policymaker, urban planner, business leader, researcher, or student, this is an essential tool for advancing sustainable urban development in our rapidly changing world.
Includes index.
Keywords: Sustainable urban development.; Architecture -- Sustainability & Green Design.; Structural engineering.; Environmentally-friendly (green) architecture and design.; Sustainability.; elektronické knihy; electronic books